DIAGENESIS AND INCIPIENT METAMORPHISM IN THE WESTERN FOLD-AND-THRUST BELT, SW URALS, RUSSIA - Glasmacher U.A.; Matenaar I.; Bauer W.; Puchkov V.N. (My University, 2004)
In the western fold-and-thrust belt of the southern Urals, the Kbler and rkai indices determined on shales, slates and phyllites record an increase from lower late diagenetic to epizonal grade from west to east. The metamorphic grade varies strongly within the different tectonic segments, which are separated by major thrusts. The increase of diagenetic and incipient metamorphic grade from the footwall to the hanging wall of all major Upper Palaeozoic thrusts indicates a pre-Permo/Triassic origin. West of the Avzyan thrust zone, the diagenetic to incipient metamorphic grade is related to the Palaeozoic basin development and reached the final grades in Late Carboniferous to Early Permian times. East of the first Avzyan thrust in the Yamantau anticlinorium, the diagenetic to lower greenschist metamorphic grade is possibly of Neoproterozoic origin and might be related to the development of the Neoproterozoic basin at the eastern margin of the East European Craton. The eastern part of the Yamantau anticlinorium was exhumed below 200C in the Late Carboniferous or Early Permian. The diagenetic grade of the autochthonous Palaeozoic sedimentary units increases toward the stack of Palaeozoic nappes and might partly be caused by the deformational process due to the emplacement of the Palaeozoic nappes. Within the Timirovo thrust sheet, the decrease of metamorphic grade with stratigraphic age developed prior to the emplacement of the nappes. The upper anchizonal metamorphic grade of the Upper Devonian slates of the Zilair nappe results from the deformation process related to the Lower Carboniferous nappe emplacement.